1999
DOI: 10.1677/erc.0.0060139
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of aromatase activity in breast fibroblasts: the role of interleukin-6 and prostaglandin E2.

Abstract: Prostaglandin E 2 (PGE 2 ) and cytokines, such as interleukin-6 (IL-6) or tumour necrosis factor α (TNFα) can regulate aromatase activity. In the present study we have compared their abilities to stimulate aromatase activity in fibroblasts derived from 'normal' breast adipose tissue proximal to a tumour or breast tumours. PGE 2 , TNFα and IL-6 plus its soluble receptor (IL-6sR) all increased aromatase activity in these cells. Basal aromatase activity and the degree of aromatase stimulation by these factors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 30 publications
2
37
0
2
Order By: Relevance
“…Although IL-6 expression in early-stage breast carcinomas has been correlated with low grade, oestrogen receptor status and good prognosis (Fontanini et al, 1999;Karczewska et al, 2000), several studies have shown that IL-6 may contribute to disease progression, particularly in advanced breast cancer patients. Indeed, IL-6 can modulate steroid hormone responsiveness by increasing aromatase activity and oestradiol 17 beta-hydroxysteroid dehydrogenase activity in malignant tissue and by activating oestrogen receptor-a (Duncan et al, 1994;Singh et al, 1999;Speirs et al, 2000). IL-6 may promote cell migration by activating the mitogen-dependent protein kinase pathway, and increase chemotherapeutic resistance by inhibiting the activation of proteases involved in apoptosis (Lotem and Sachs, 1997;Badache and Hynes, 2001).…”
Section: Prognostic Value Of Angiogenic Factors In Breast Cancer T Bamentioning
confidence: 99%
“…Although IL-6 expression in early-stage breast carcinomas has been correlated with low grade, oestrogen receptor status and good prognosis (Fontanini et al, 1999;Karczewska et al, 2000), several studies have shown that IL-6 may contribute to disease progression, particularly in advanced breast cancer patients. Indeed, IL-6 can modulate steroid hormone responsiveness by increasing aromatase activity and oestradiol 17 beta-hydroxysteroid dehydrogenase activity in malignant tissue and by activating oestrogen receptor-a (Duncan et al, 1994;Singh et al, 1999;Speirs et al, 2000). IL-6 may promote cell migration by activating the mitogen-dependent protein kinase pathway, and increase chemotherapeutic resistance by inhibiting the activation of proteases involved in apoptosis (Lotem and Sachs, 1997;Badache and Hynes, 2001).…”
Section: Prognostic Value Of Angiogenic Factors In Breast Cancer T Bamentioning
confidence: 99%
“…The fact that tumour oestradiol concentration is often higher than the concentration seen in surrounding non-malignant tissue is consistent with local synthesis but also high concentration of the 17b-hydroxysteroid reductase in the tumours (vanLandeghem et al 1985, Vermeulen et al 1985. While the aromatase enzyme expressed in different tissues is the same, a number of different promoters have been identified as playing a different role in different compartments (Chen et al 2001, Bulun et al 2003, suggesting potential local regulation by hormones, growth factors and interleukins (Reed et al 1993, Zhao et al 1995, 1996, Agarwal et al 1996, Simpson et al 1999, Singh et al 1999. Notably, while tissue concentrations of oestradiol are high, we and others have found the concentration of oestrone sulphate to be somewhat lower in tissue compared with the circulation (Vermeulen et al 1985, Geisler et al 2001.…”
Section: Endocrine Rationale For Aromatase Inhibitionmentioning
confidence: 85%
“…There is evidence, however, that PGE 2 may act, in part, to stimulate aromatase activity by the induction of IL-6 (Singh et al, 1999). As Sant 7 effectively blocks stimulation of aromatase activity by IL-6+IL-6sR, it was used to obtain further insight into its regulation by IL-6 or PGE 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts derived from normal or malignant breast tissues have been used as a model to investigate aromatase activity as these cells have a much higher level of activity than epithelial cells (Singh et al, 1999). Using such fibroblasts a number of cytokines including interleukin 6 (IL-6) and tumour necrosis factor a (TNFa) were identified as important regulators of fibroblast aromatase activity (Reed et al, 1992;Macdiarmid et al, 1994).…”
mentioning
confidence: 99%